2015
DOI: 10.1016/j.celrep.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Microglia-Secreted Galectin-3 Acts as a Toll-like Receptor 4 Ligand and Contributes to Microglial Activation

Abstract: Inflammatory response induced by microglia plays a critical role in the demise of neuronal populations in neuroinflammatory diseases. Although the role of toll-like receptor 4 (TLR4) in microglia's inflammatory response is fully acknowledged, little is known about endogenous ligands that trigger TLR4 activation. Here, we report that galectin-3 (Gal3) released by microglia acts as an endogenous paracrine TLR4 ligand. Gal3-TLR4 interaction was further confirmed in a murine neuroinflammatory model (intranigral li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
300
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 296 publications
(330 citation statements)
references
References 53 publications
16
300
1
Order By: Relevance
“…Several studies using different experimental models, have indicated that galectin-3 plays a key role in recruitment and activation of neutrophils, monocytes, macrophages and microglia, and its absence leads to a decrease in recruitment of inflammatory cells to the injured tissue and their activation in it (Alves et al, 2010;Farnworth et al, 2008;Jiang et al, 2009;Nieminen et al, 2005;Rotshenker, 2009;Rotshenker et al, 2008). Nowadays, there is a growing body of evidence demonstrating the importance of this protein after pathologic, inflammatory and traumatic injuries to the CNS (Burguillos et al, 2015;Jiang et al, 2009;Manouchehrian et al, 2015;Pajoohesh-Ganji et al, 2012) however, up to now there are no reports in the literature describing the spatiotemporal changes after SCI in the absence of galectin-3.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies using different experimental models, have indicated that galectin-3 plays a key role in recruitment and activation of neutrophils, monocytes, macrophages and microglia, and its absence leads to a decrease in recruitment of inflammatory cells to the injured tissue and their activation in it (Alves et al, 2010;Farnworth et al, 2008;Jiang et al, 2009;Nieminen et al, 2005;Rotshenker, 2009;Rotshenker et al, 2008). Nowadays, there is a growing body of evidence demonstrating the importance of this protein after pathologic, inflammatory and traumatic injuries to the CNS (Burguillos et al, 2015;Jiang et al, 2009;Manouchehrian et al, 2015;Pajoohesh-Ganji et al, 2012) however, up to now there are no reports in the literature describing the spatiotemporal changes after SCI in the absence of galectin-3.…”
Section: Discussionmentioning
confidence: 97%
“…MacKinnon et al (2008) showed that galectin-3 RNA inhibition in macrophages, blocked the alternative macrophage activation mediated by IL-4, while the classical activation mediated by IFN-γ and bacterial membrane lipopolysaccharide (LPS), was not affected . In a recent manuscript, Burguillos et al (2015) demonstrated, in vitro and in vivo, that galectin-3 has a strong effect on microglial cell activation through interaction with Toll-like 4 receptors (TLR4), inducing these cells to express pro-inflammatory molecules. Differing from the observations of MacKinnon et al (2008), they found that the inhibition of galectin-3 facilitates macrophage polarization into M2 phenotypes in vitro.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, recent studies by Burguillos and colleagues elegantly showed that Gal-3 serves as an endogenous paracrine ligand for TLR4 on microglia cells, shifting the balance toward an M1-type phenotype, which accentuates CNS inflammation [135]. In accordance with these findings, cuprizone (CPZ)-treated mice displayed heightened M1 microglial activation associated with ectodermal dysplasia protein 1 (ED1) expression and pronounced upregulation of the phagocytic triggering receptor expressed on myeloid cells 2 (TREM-2b), while this effect was not observed in CPZ-treated Lgals3 À/À mice [136].…”
Section: Alternatively-activated M2-type Macrophages and Microgliamentioning
confidence: 99%
“…A recent study reported that galectin-3 (Gal-3)-TLR-4 interaction is related to neuroinflammation in a mouse model [18]. Currently, 14 mammalian galectins have been reported, and they can be divided into three groups: prototype (Gal-1, -2, -5, -7, -10, -11, -13, and -14), chimera (Gal-3), and tandem repeat (Gal-4, -6, -8, -9, and -12).…”
Section: Introductionmentioning
confidence: 99%